PENGARUH SOFT SKILL DAN HARD SKILL TERHADAP KESIAPAN KERJA MAHASISWA DI BANK SYARIAH - Sari, Cici Nur Indah; Manunggal, Syafrudin Arif Marah (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
To the best work outcomes and collaboration in the workplace, work readiness must meet organized and methodical requirements. The mastery of Soft Skills and Hard Skills shows the employment readiness of graduates to become a professional workforce and ready to compete in the world of work. The aim of this study is to know the influence of Soft Skill and Hard Skill on the preparation for work in Syrian banking students UIN Sayyid Ali Rahmatullah Tulungagung. This research is associative in nature with the type of data used is primary data through the dissemination of questionnaires. Respondents in this study were Syrian banking students UIN Sayyid Ali Rahmatullah Tulungagung with a total of 472 students with sampling methods. The data analysis methods used are data instrument testing, classical assumption testing and double linear regression analysis. The results of this study suggest that, simultaneously (together) as well as partially Soft Skill and Hard Skill have a positive and significant impact on work readiness, which means that the better Soft Skills and Hard Skills, the better a person’s working readiness to compete in the world of work is also better and increases.